Envisioning Uncertain Futures Scenarios as a Tool in Security, Privacy and Mobility Research (Zukunft und Forschung, 2018)
This book contains a collection of projects and scenarios dealing with new risks from emerging technologies, future peace keeping operations, and water distribution issues by combining analysis with dialogue. Special attention is paid to the methodology of narrative scenarios, and the role of imagination in the generation of these scenarios. Appearing as short stories, narrative scenarios include a great amount of explicit and implicit knowledge and they need story telling skills to become consistent, coherent as well as compelling and convincing pictures of the future. Contents Narrative Scenarios Public Security Future of Water Use Future of Peace Operations Emerging Technological Threats Target Groups Researchers, lectures and students of social and political sciences, management, communication and education with interest in foresight Practitioners from think tanks and consultancies, from risk and security research, technology foresight and technology assessment The Editors Roman Peperhove is head of the research Unit for Public Security at Freie Universität Berlin. Dr. Karlheinz Steinmüller is scientific director of a foresight consulting company and science fiction author. Prof. Dr. Hans-Liudger Dienel holds the professorship "Arbeitslehre/Technik und Partizipation" at the Technical University of Berlin and is Managing Director of the nexus Institute for Cooperation Management and Interdisciplinary Research GmbH.